Influence of Dynamic Load on Soil Moisture Field in the Process of Freeze-Thaw Cycles - Yongting Huang; Wei Ma; Donghui Xiao; Yuezhen Xu (Advances in Materials Science and Engineering)
Due to climate warming and large-scale engineering activities, the embankment engineering risk in the permafrost and seasonally frozen regions caused by water content change in the soil has become more and more serious. To study the moisture migration law in the embankment under the vehicle load action and periodic variation of temperature, a series of temperature-controlled model tests under the dynamic load condition were carried out, the dynamic load was imposed by an air hammer connecting a vibration plate, which was installed on the top surface of the soil, and the variation law of the temperature and moisture fields in the model was analyzed. The test results show that the moisture field in the soil sample changes obviously with the increasing freeze-thaw cycles under the no-load condition, especially after nine freeze-thaw cycles, two moisture accumulation areas appear in the range of 8–15 cm from the soil surface; the dynamic load has an inhibitory effect on the moisture migration within 5 cm below the vibration plate and has a promoting effect on the range of 10–30 cm below the vibration plate. With the increase in the number of freeze-thaw cycles, three high-water content areas are gradually formed and approximately uniformly distributed within the 10–25 cm depth range of the soil, which has an important impact on the stability of the soil. The water content of the moisture accumulation areas during freezing is greater than that during thawing under the no-load condition, while the water content of the moisture accumulation areas during freezing is less than that during thawing under dynamic load. The research results can provide references for the embankment design and disease treatment in cold regions.